Título Padrão - Galdino Nascimento, Cicero Antonio (Revista Vazantes, 2021)
The current video, titled As Cantigas de Memória do Belmonte, makes reference to one of the musical practices of orality that constitutes the cultural tradition of the district of Belmonte, located in the city of Crato, Ceará. The aim of this production is to highlight musical experiences that make up the life stories of elderly women and elders in this community, guardians of the cultural memory of their people. It was possible to note that the songs reveal life narratives, based on respect for the popular and religious traditions of its people, whom also cultivated music making as a pulsating exercise of various daily activities, being, therefore, an important element for the construction of local cultural identity. In conclusion, we intend to show a memorialistic repertoire of oral tradition, the result of community-driven experiences.